Peranan Pokdarwis dalam mengembangkan wisata agropolitan di Desa Poncokusumo Kecamatan Poncokusumo Kabupaten Malang - Dina Rahma Ardhiana; Sukamto Sukamto; Agus Purnomo; I Nyoman Ruja; Mely Kurnia (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2022)
This study aims to describe the role Pokdarwis in developing agropolitan travel Poncokusumo Poncokusumo District of Malang. The research approach used is qualitative descriptive research. Source data used are primary data and secondary data. Data collection techniques are observation, interview and documentation. Analysis of data using an interactive model of Miles & Huberman with the data collection phase, data reduction, data presentation, and conclusion or verification. The results showed that the role of people who become members of Pokdarwis in developing Agropolitan travel can be seen from three stages: planning, implementation and evaluation. In the planning stage Agropolitan travel Pokdarwis follow Musrenbang and decision making. The implementation stage Agropolitan travel Pokdarwis involved in the supply of land, coordinating, following the community development activities organized by the government and maintain infrastructure and engage in discussions on the evaluation of the evaluation stage. The role of the community who are members of Pokdarwis in developing agropolitan Poncokusumo travel is good enough because people have their own initiatives to develop agropolitan travel. however The role of the community who are members of Pokdarwis in developing agropolitan Poncokusumo travel is good enough because people have their own initiatives to develop agropolitan travel. however The role of the community who are members Pokdarwis in developing agropolitan Poncokusumo travel is good enough because people have their own initiatives to develop agropolitan travel. However there needs to be a synergy between the government and society, and the strategy for Agropolitan travel can develop optimally. Penelitian ini bertujuan mendeskripsikan peranan Pokdarwis dalam mengembangkan wisata agropolitan di Desa Poncokusumo Kecamatan Poncokusumo Kabupaten Malang. Pendekatan penelitian yang digunakan adalah kualitatif dengan jenis penelitian deskriptif. Sumber data yang digunakan adalah data primer dan data sekunder. Teknik pengumpulan data adalah observasi, wawancara dan dokumentasi. Analisis data menggunakan model interaktif Miles & Huberman dengan tahap pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Hasil penelitian menunjukkan bahwa peranan masyarakat yang menjadi anggota Pokdarwis dalam mengembangkan wisata agropolitan dapat dilihat dari 3 tahap yaitu perencanaan, pelaksanaan dan evaluasi. Pada tahap perencanaan Pokdarwis wisata agropolitan mengikuti kegiatan Musrenbang dan pengambilan keputusan. Tahap pelaksanaan Pokdarwis wisata agropolitan terlibat dalam dengan menyediakan lahan, melakukan koordinasi, mengikuti kegiatan pemberdayaan masyarakat yang diadakan oleh pemerintah dan memelihara sarana prasarana serta terlibat dalam diskusi evaluasi pada tahap evaluasi. Peranan masyarakat yang menjadi anggota Pokdarwis dalam mengembangkan wisata agropolitan di Desa Poncokusumo sudah cukup baik karena masyarakat mempunyai inisiatif sendiri untuk mengembangkan wisata agropolitan. Namun perlu ada sinergitas antara pemerintah dan masyarakat, dan strategi agar wisata agropolitan bisa berkembang secara maksimal.